Influence of Social Media Influencers on Parasocial Interaction Impacts Value Perception and Purchase Intention Luxury Bags - Maryanto, Syifa; Royhana, Ajib; Dhamatiyo, Revaldi; Setiowati, Rini (Yayasan Ilomata, 2024)
This study aims to determine social media influencers, which in this case is measured based on attractiveness (social and physical) to parasocial interaction, as well as the effect of Parasocial Interaction on the value perception of luxury goods (social, personal, and conspicuous) on social media. This research is also conducted to determine whether value perception and parasocial interaction can influence purchase intention. In addition, this research will focus on one product, namely luxury bags. To achieve the research objectives and test the research model, a database-based questionnaire was developed and distributed to 350 respondents in Indonesia through an online platform. This research utilizes the Partial Least Squares Structural Equation Modelling (PLS-SEM) method. The results of this study indicate that the attractiveness of Social Media Influencers has an influence on Parasocial Interaction, besides that Parasocial Interaction can build Luxury Brand Value Perception. This study also shows that Value Perception affects on Purchase Intention. Meanwhile, Parasocial Interaction have no significant effect on Purchase Intention. The findings of this study have important implications for marketers and influencer in designing more effective marketing strategies to increase the value perception and purchase intention of consumers towards luxury bags.